A simple sufficient condition for triviality of obstructions in the orbifold construction for subfactors - Masuda, Toshihiko (MATHEMATICA SCANDINAVICA, 2017)
We present a simple sufficient condition for triviality of obstructions in the orbifold construction. As an application, we can show the existence of subfactors with principal graph $D_{2n}$ without full use of Ocneanu's paragroup theory.